Multi-transitivity of semigroup actions. Issue 9 (2nd September 2021) - Wang, Huoyun; Fang, Junyan; Zhong, Xinlin
Abstract : Moothathu [Colloq. Math. 120 (2010), pp. 127–138] proved that multi-transitivity, weakly mixing and Δ-transitivity are equivalent for minimal homeomorphisms. In this paper, we extend this result to Abelian group actions. Moreover, we point out that a multi-transitive system of Abelian group action is Li–Yorke ε -chaotic for some ε > 0 .